MH17: How safe are the skies? - Mohd Rusli, Mohd Hazmi; Mohamad, Rahmat (2014)
From the earliest kites to hypersonic flights, the history of aviation extends to more than a thousand years. The flying machine created by the Wright Brothers gradually changed the world’s transportation industry.Commercial flights or airlines were subsequently introduced to replace sea transportation as the fastest way to convey people to various destinations around the world. The Malayan Airways came into the picture in 1947. Upon Malaysia’s independence and separation of Singapore, the Malaysia Airlines System (MAS) was founded in 1972, serving not only Malaysia, but the world.The recent MH17 tragedy is a tragic episode in global aviation history when the world is still mourning over the disappearance of MH370. These tragedies may lead to one simple question – how safe are the skies? This paper discusses how international law through the Chicago Convention regulates safe overflight and assisted in developing the aviation industry. This paper further explains that the gunning down of MH 17 was a blatant violation of international law and MAS should not be blamed and lambasted for this tragedy. This article concludes that the skies are not entirely safe for the normal practice of civil aviation and that the world community should work together in ensuring that MH 17 tragedy would not happen again.